Civic Cultural Literacy Research Trend in Primary Schools: Tren Penelitian Literasi Budaya Kewarganegaraan di Sekolah Dasar - Syamsijulianto, Tri; Sapriya; Udin Syaefudin Sa’ud; Cepi Riyana; Tio Gusti Satria; Pranata, Alvira (Elementary Teacher Education Program, Majalengka University, 2024)
This study uses VOSviewer bibliometric analysis to chart the upward trajectory of civic cultural literacy research, particularly in primary schools. The goal of this study was to examine civic cultural literacy research trends using bibliometric analysis. Article data were collected using publication reference management systems and the Publish or Perish (PoP 8) database. Direct the search process by including the keywords